Functional Aspects of Pragmatics tn the Text - Yuldosheva Mavjuda Khairullayevna (Indonesian Journal of Innovation Studies, 2022)
The article provides an overview of text creation and the importance of pragmatics in text creation. At the same time, the text also provides insights into the functional aspects of pragmatics. In addition, all features were analyzed using comprehensive examples.